Awareness of post partum intra uterine contraceptive device and reasons for its low acceptance in an urban Indian population - Chawla, Raina; Ahuja, Rashmi; Sharma, Priyanka (International Journal of Research in Medical Sciences, 2020)
Background: The safety and efficacy of the Post-Partum Intra Uterine Contraceptive Device (PPIUCD) has been documented worldwide. With increasing institutional deliveries and greater sensitization, the aim is to increase PPIUCD insertions. Many areas still report poor acceptance. Objectives of this study to determine the proportion of antenatal women willing to accept PPIUCD insertion and the reasons behind refusal to accept this method. Methods: A prospective questionnaire study was done between January 2019 to June 2019 of 200 women. Inclusion criteria were antenatal women in the 2nd/3rd trimester. Exclusion criteria were those opting for a permanent method of contraception and those with a contra-indication. Results: Eighty-four women (42%) had never used any method of contraception. Earlier Intrauterine device (IUD) use (including both interval and PPIUCD) was in only 18.9% of all contraceptive users. Only 2 women in the group had ever used PPIUCD. 79% of women were aware of IUDs. Those unaware were mainly nulliparous. Amongst those aware of an IUD, 88 (56%) were aware it could be inserted postpartum. Only 18% were aware it could be inserted intra-cesarean. All women who participated were offered the option for a PPIUCD. Fifty-nine (29.5%) of all women expressed their willingness but on follow up till delivery only 18 of these women got a PPIUCD inserted. Amongst those not willing for the PPIUCD insertion the commonest reason was general apprehension (39%) followed by partner refusal (33%) and fear of complications (31%). Six women (4.2%) gave history of complications following earlier use and were unwilling for its repeat use. Conclusion: The large unmet need for contraception in India can be solved through repeated counselling and discussions with the woman during her antenatal visits. Alleviating apprehension and addressing concerns of the couple will increase PPIUCD acceptance.